CircRNA_0075723 protects against pneumonia-induced sepsis through inhibiting macrophage pyroptosis by sponging miR-155-5p and regulating SHIP1 expression - Yang, Dianyin; Zhao, Dongyang; Ji, Jinlu; Wang, Chunxue; Liu, Na; Bao, Xiaowei; Liu, Xiandong; Jiang, Sen; Zhang, Qianqian; Tang, Lunxian (Frontiers in Immunology, 2023)
Introduction Circular RNAs (circRNAs) have been linked to regulate macrophage polarization and subsequent inflammation in sepsis. However, the underlying mechanism and the function of circRNAs in macrophage pyroptosis in pneumonia-induced sepsis are still unknown. Methods In this study, we screened the differentially expressed circRNAs among the healthy individuals, pneumonia patients without sepsis and pneumonia-induced sepsis patients in the plasma by RNA sequencing (RNA-seq). Then we evaluated macrophage pyroptosis in sepsis patients and in vitro LPS/nigericin activated THP-1 cells. The lentiviral recombinant vector for circ_0075723 overexpression (OE-circ_0075723) and circ_0075723 silence (sh-circ_0075723) were constructed and transfected into THP-1 cells to explore the potential mechanism of circ_0075723 involved in LPS/nigericin induced macrophage pyroptosis. Results We found circ_0075723, a novel circRNA that was significantly downregulated in pneumonia-induced sepsis patients compared to pneumonia patients without sepsis and healthy individuals. Meanwhile, pneumonia-induced sepsis patients exhibited activation of NLRP3 inflammasome and production of the pyroptosis-associated pro-inflammatory cytokines IL-1β and IL-18. circ_0075723 inhibited macrophage pyroptosis via sponging miR-155-5p which promoted SHIP1 expression directly. Besides, we found that circ_0075723 in macrophages promoted VE-cadherin expression in endothelial cells through inhibiting the release of NLRP3 inflammasome-related cytokines, IL-1β and IL-18, and protects endothelial cell integrity. Discussion Our findings propose a unique approach wherein circ_0075723 suppresses macrophage pyroptosis and inflammation in pneumonia-induced sepsis via sponging with miR-155-5p and promoting SHIP1 expression. These findings indicate that circRNAs could be used as possible potential diagnostic and therapeutic targets for pneumonia-induced sepsis.